Phosphogypsum and its Potential Use in Croatia: Challenges and Opportunities - Bituh, Tomislav (Arh Hig Rada Toksikol, 2021)
Phosphogypsum (PG) is a waste by-product (residue) originating from the production of phosphoric acid and phosphate fertilisers. PG contains chemical and radioactive impurities, which is why it is mostly stockpiled in controlled areas. Worldwide, only about 15 % of PG is recycled or reused. Today, policies and business strategies prioritise sustainable development through circular economy, which certainly includes PG. This provides new opportunities for Croatia to manage its PG and make an effort to use it as an additive in different industries, such as agriculture and construction. Due to its chemical and radiological properties, PG can potentially cause problems for the environment and human health. Hence, before using PG, detailed knowledge of potential hazards is necessary to protect people and the environment. The aim of this review is to summarise available data on Croatian PG, compare them with other countries, and to identify knowledge gaps and the lack of data on potential hazardous substances in PG in order to assess the opportunities of using PG in Croatia.